ANALYSIS OF FASTENING METHODS DURING THE TRANSPORTATION OF WEAPONS AND MILITARY EQUIPMENT BY RAIL TRANSPORT - Bekh, P. V.; Gudimov, V. V.; Maksimenkov, Ye. A. (Systems and Technologies, 2023)
The purpose of the work is to conduct an analysis of the organization of continuity transportation of military units of the Armed Forces of Ukraine. Currently, the issue of readiness to move military units (units) in a short period of time, without violating their integrity, with the provision of the possibility of a sudden transition to the performance of assigned tasks, which is an integral component of military operations (combat operations), is important. Problematic issues during the loading of military echelons and transports in modern conditions are highlighted. Comprehensive measures aimed at optimizing the time spent on loading and unloading operations have been determined. On the basis of the conducted analysis, conclusions were made about the need to create and manufacture sets of universal multi-turn fasteners for each technique. The success of military transportation depends primarily on the organization of close cooperation between the military management bodies and the management bodies on the types of transport, on the timely and high-quality preparation of the military unit for transportation. Interaction with the management bodies on the types of transport is carried out on the issues of ensuring and regulating military transports, coordination of technical capabilities and control of preparations for carrying out transports. Scientific novelty. It consists in setting the task of preparing military equipment for transportation to the exit of echelon units to the loading station. Also, simultaneously with the preparation of the equipment, the procurement of fastening materials and devices takes place.